PT Pos Indonesia Public Service Innovation in Maintaining Existence and Competitiveness in the Industrial Era 4.0 (Case Study of PT Pos Indonesia KC Subang) - Asep Mustopa Saputra; Dini Aulia Ilmi; Windi Angelina; Silvy Sondari Gadzali; Abu Muna Almaududi Ausat (Departement of Mathematics Education, 2023)
In the era of the Information Technology Industry, the function of the post office experienced a shift and had a major impact on Indonesian society. The large number of new private companies engaged in the same field has created intense competition, therefore PT Pos has transformed public service innovations in maintaining its existence and competitiveness. In this study using a qualitative descriptive method. The sources of data obtained are primary sources, namely obtained directly from informants and secondary sources obtained through previous journals, archives, articles and related books. The subject of this research is one of the Subang Post Office employees. This research is located at the Subang Branch Post Office. Data analysis used the Miles and Hubermas technique, starting from data collection, data presentation, reduction and finally drawing conclusions. The results of the study show that 1) Forms of service innovation at PT. Pos Indonesia Subang 2) PT. Pos Indonesia has succeeded in innovating because of existing service innovations, such as the Q9 service, the PosAja digital outlet application! And PospayMobile which has new characteristics that are more effective and efficient by utilizing online network technology so that it can be accepted by the service user community. 3) The condition of PT Pos is after Innovation. With innovation, you can improve the quality of services provided by the post office. Even though there are still several constraining factors, the Subang post office continues to innovate for the needs of the community